PEWARISAN BERDASARKAN HUKUM WARIS ADAT TERKAIT SISTEM KEKERABATAN DI INDONESIA - Subekti Subekti; Suyono Yoyok Ucuk (Jurnal Aktual Justice, 2020)
There are three kinds of inheritance law in Indonesia, namely Islamic inheritance, Customary inheritance and BW inheritance. The scope of this writing is limited to customary inheritance law. The parts of customary law have a big influence on customary inheritance law and vice versa. Customary inheritance law has its own characteristics and characteristics that are unique to Indonesia, which is different from Islamic law and western law (BW). Because the difference lies in the natural background of the Indonesian people who have the philosophy of Pancasila with a society that is Bhinneka Tunggal Ika. The inheritance law that exists and applies in Indonesia to date is still not in the form of legal unification. The purpose of this study is to analyze the inheritance system according to the customary inheritance law related to the kinship system in Indonesia.The type of research used in this research is normative juridical research, namely research on legal systematic is research conducted on primary and secondary legal materials, the terms of reference used are the basic definitions contained in the legal system. The approach used is a conceptual approach, a statute approach and a case approach. Types of Legal Materials are primary legal materials and secondary legal materialsThe results of this study indicate that the inheritance system according to the Adat Inheritance Law does not refer to the kinship system of the customary law community. Customary law communities whose system of collective inheritance can occur are parental kinship systems. Heritage assets related to inheritance must be distinguished from the origin of the assets, because they are related to the kinship system that exists in the local customary law community, whether parental, patrilineal or matrilineal, because not all inheritance can be divided individually.